2022
DOI: 10.1155/2022/1802706
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Biomarkers for Progression and Prognosis of Bladder Cancer by Comprehensive Bioinformatics Analysis

Abstract: Background. Bladder cancer (BLCA) is a highly malignant tumor that develops in the urinary system. Identification of biomarkers in progression and prognosis is crucial for the treatment of BLCA. BLCA-related differentially expressed genes (DEGs) were authenticated by screening the DEGs and weighted gene coexpression network analysis (WGCNA). LASSO and SVM-RFE algorithms were utilized to screen the feature genes in BLCA. Survival analysis was performed using the Kaplan–Meier curve provided by the ‘survival’ R p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…We also found that a higher level of ATP1A2 was associated with shorter overall survival time in GC patients, which was consistent with the effect of ATP1A2 on prognosis in ovarian cancer and bladder cancer. 45 , 47 In addition, this result was validated in other independent datasets. These results indicated that ATP1A2 has potential as a tumor promoter and its high expression was significantly associated with poor prognosis in patients with GC.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We also found that a higher level of ATP1A2 was associated with shorter overall survival time in GC patients, which was consistent with the effect of ATP1A2 on prognosis in ovarian cancer and bladder cancer. 45 , 47 In addition, this result was validated in other independent datasets. These results indicated that ATP1A2 has potential as a tumor promoter and its high expression was significantly associated with poor prognosis in patients with GC.…”
Section: Discussionsupporting
confidence: 64%
“…This abnormal expression is thought to play a role in the development and onset of cancer. 44 , 45 In addition, ATP1A2 suppressed invasion, migration, apoptosis, and proliferation in prostate cancer by inactivating the Smad/TGF-β pathway. 46 In our study, the results of multiple databases showed that ATP1A2 was down-regulated in GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Crosstalk between cancer cells and the TME has been proven to play an important role in tumor progression and metastasis ( 43 ). And TIICs are an important component of the TME, and their composition and distribution are closely related to tumorigenesis and development ( 44 ). First, we explored the correlation between risk score and infiltrating immune cell abundance according to XCELL, TIMER, QUANTISEQ, MCPCOUNTER, CIBERSORT, CIBERSORT-ABS and EPIC algorithms, where the CD8+ T cell, NK cell infiltration were all positively correlated with the risk score ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been established that the interaction between cancer cells and the TME is critical for the development and spread of tumors 47 . An essential part of the TME is TIICs, whose distribution and composition are intimately linked to tumor growth 46 , 48 . Using the XCELL, TIMER, QUANTISEQ, MCPCOUNTER, CIBERSORT, CIBERSORT-ABS, and EPIC algorithms, we first investigated the relationship between risk ratings and the quantity of invading immune cells.…”
Section: Resultsmentioning
confidence: 99%